Genetic influences on dental enamel that impact caries differ between the primary and permanent dentitions - Bayram, Merve; Deeley, Kathleen; Reis, Maria; Trombetta, Vanessa; Ruff, Timothy; Sencak, Regina; Hummel, Michael; Dizak, Piper; Washam, Kelly; Romanos, Helena; Lips, Andrea; Alves, Gutemberg; et al. (Wiley, 2015)
Clinically, primary and permanent teeth are distinct anatomically and the presentation of caries lesions differs between the two dentitions. Hence, the possibility exists that genetic contributions to tooth formation of the two dentitions are different. The purpose of this study was to test the hypothesis that genetic associations with an artificial caries model will not be the same between primary and permanent dentitions. Enamel samples from primary and permanent teeth were tested for microhardness at baseline, after carious lesion creation, and after fluoride application to verify association with genetic variants of selected genes. Associations were found between genetic variants of ameloblastin, amelogenin, enamelin, tuftelin, tuftelin interactive protein 11, and matrix metallopeptidase 20 and enamel from permanent teeth but not with enamel from primary teeth. In conclusion, our data continue to support that genetic variation may impact enamel development and consequently individual caries susceptibility. These effects may be distinct between primary and permanent dentitions.
WOS: 000361490800004
PubMed ID: 26283008
Keywords: Dental Caries; Dentition; Enamel Microhardness; Permanent; Primary